2019
DOI: 10.1039/c8fo01777h
|View full text |Cite
|
Sign up to set email alerts
|

Dietary wild bitter gourd displays selective androgen receptor modulator like activity and improves the muscle decline of orchidectomized mice

Abstract: Wild bitter gourd, like selective androgen receptor modulators (SARMs), restored the mass of androgen responsive muscles but not prostate and might improve skeletal muscle function in orchidectomized mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Skeletal muscle is the main source for proteins in animals and is one of the main organs involved in energy acquisition and maintenance. The weight and size of muscle mass respond very rapidly to hormone stimulation during anabolism or catabolism [19,20]. Previous study showed that androgens promoted muscle growth by maintaining myoblasts in the proliferate state and delaying the differentiation process [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle is the main source for proteins in animals and is one of the main organs involved in energy acquisition and maintenance. The weight and size of muscle mass respond very rapidly to hormone stimulation during anabolism or catabolism [19,20]. Previous study showed that androgens promoted muscle growth by maintaining myoblasts in the proliferate state and delaying the differentiation process [8].…”
Section: Discussionmentioning
confidence: 99%
“…In males, androgens acted through AR to regulate multiple signalling pathways that control muscle mass, strength and fatigue resistance [1]. Studies of muscle-specific ARKO mouse models provided evidence that a direct role of AR in hind limb muscles was to regulate their strength and fiber type distributions, and it was also a major muscle quality determinant [11,19]. In this study, the expression of endogenous AR mRNA increased gradually following embryonic development, and it was higher in females than that of males (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%